Letter (copy) : Goods for Spain - Citrine, Walter, 1887-1983
028-0089-001 WMC/HVT/FC/454. Secretary's. 21st January, 1937. Mr. G. Stolz, The International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS, VIIe. Dear Mr. Stolz, GOODS FOR SPAIN. Further to my letter of the 19th instant I have this morning heard from the Co-operative Wholesale Society that the S.S. PELAYO will not be sailing until Tuesday next, January 26th. Yours sincerely, General Secretary. 292/946/28/89